Science‐Based Approach to Harmonize Contraception Recommendations in Clinical Trials and Pharmaceutical Labels. Issue 2 (5th May 2022) - Bowman, Christopher J.; Becourt‐Lhote, Nathalie; Boulifard, Virginie; Cordts, Rüdiger; Corriol‐Rohou, Solange; Enright, Brian; Erkman, Linda; Harris, Jayne; Hartmann, Andreas; Hilpert, Jan; Kervyn, Sophie; Mattson, Britta; et al.
Abstract : This review presents a European Federation of Pharmaceutical Industries and Association/PreClinical Development Expert Group (EFPIA‐PDEG) topic group consensus on a data‐driven approach to harmonized contraception recommendations for clinical trial protocols and product labeling. There is no international agreement in pharmaceutical clinical trial protocols or product labeling on when/if female and/or male contraception is warranted and for how long after the last dose. This absence of consensus has resulted in different recommendations among regions. For most pharmaceuticals, contraception recommendations are generally based exclusively on nonclinical data and/or mechanism. For clinical trials, contraception is the default position and is maintained for women throughout clinical development, whereas appropriate information can justify removing male contraception. Conversely, contraception is only recommended in product labeling when warranted. A base case rationale is proposed for whether or not female and/or male contraception is/are warranted, using available genotoxicity and developmental toxicity data. Contraception is generally warranted for both male and female subjects treated with mutagenic pharmaceuticals. We propose as a starting point that contraception is not typically warranted when the margin is 10‐fold or greater between clinical exposure at the maximum recommended human dose and exposure at the no observed adverse effect level (NOAEL) for purely aneugenic pharmaceuticals and for pharmaceuticals that induce fetal malformations or embryo‐fetal lethality. Other factors are discussed, including contraception methods, pregnancy testing, drug clearance, options for managing the absence of a developmental toxicity NOAEL, drug‐drug interactions, radiopharmaceuticals, and other drug modalities. Overall, we present a data‐driven rationale that can serve as a basis for consistent contraception recommendations in clinical trials and in product labeling across regions.